Preparation of Azithromycin Nanofibers as Controlled Release Ophthalmic Drug Carriers Using Electrospinning Technique: In Vitro and In Vivo Characterization - Shiva Taghe; Saba Mehrandish; Shahla Mirzaeei (Tabriz University of Medical Sciences, 2022)
Purpose: Conventional topical dosage forms face with some challenges like low intraocularbioavailability, which could be overcome by application of novel drug delivery systems.Therefore, this study was conducted to prepare azithromycin (AZM)-loaded chitosan/polyvinylalcohol/polyvinyl pyrrolidone (CS/PVA-PVP) nanofibers with the prolonged antibacterialactivity by electrospinning method.Methods: After preparation of nanofibers, they were characterized in terms of physicochemicaland morphological properties. In vitro and in vivo release of the drug from nanofibers wereevaluated using microbial assay against the Micrococcus luteus. Antibacterial efficacy of thenanofibers was assessed. The ophthalmic irritation test was also performed. MTT test wascarried out to evaluate cytotoxicity of the formulations.Results: All the formulations were found to be stable with uniform thickness, weight, and drugcontent. Nanofibers had a diameter range from 119 ± 29 to 171 ± 39 nm. The inserts were nonirritantand non-toxic to the rabbits' eye. Based on the obtained results, the crosslinked AZMnanofibers showed slower and more controlled drug release in tear fluid compared to the noncrosslinkedones, within 184 hours.Conclusion: Our results revealed that the prepared nanofibers could be considered as suitableand non-invasive inserts for the prolonged ophthalmic delivery of AZM.